Are youth mentoring programs good value-for-money? An evaluation of the Big Brothers Big Sisters Melbourne Program - Fisher Jane; Moodie Marjory L (BMC, 2009)
Abstract Background The Big Brothers Big Sisters (BBBS) program matches vulnerable young people with a trained, supervised adult volunteer as mentor. The young people are typically seriously disadvantaged, with multiple psychosocial problems. Methods Threshold analysis was undertaken to determine whether investment in the program was a worthwhile use of limited public funds. The potential cost savings were based on US estimates of life-time costs associated with high-risk youth who drop out-of-school and become adult criminals. The intervention was modelled for children aged 10-14 years residing in Melbourne in 2004. Results If the program serviced 2,208 of the most vulnerable young people, it would cost AUD 39.5 M. Assuming 50% were high-risk, the associated costs of their adult criminality would be AUD 3.3 billion. To break even, the program would need to avert high-risk behaviours in only 1.3% (14/1,104) of participants. Conclusion This indicative evaluation suggests that the BBBS program represents excellent 'value for money'.